PENGUJIAN EFISIENSI PASAR BENTUK LEMAH PADA PASAR MODAL INDONESIA PERIODE 2014-2017 - Eka Yulianti; Dwi Jayanti (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2019)
Investigate the current consumption of assets for the benefit of the future. The investment canbe done by only one in the capital market which means that the investment is invested in the initialcapital assets. Profit or the same value is aimed at the investor's main interest in investing not releasedfrom risk money. Such risks are inevitably uncertain about information movement in the stock market.Relevant information available can be used as a basis for making decisions when to buy shares orretain holdings of shares. In addition, information can also be a basis for consideration when to releaseshares or not to buy shares at all. This information relates to Efficient Market Hypothesis (HPE) whichcontinues to research in financial markets. One of the forms of the Efficient Market (HPE) hypothesis isthat market efficiency is a weak form that is examined in this study. This market efficiency form isrelated to random walk theory which assumes that past data is not related to present value.